EFFORTS TO IMPROVE LANGUAGE LEARNING OUTCOMES THROUGH COOPERATIVE LEARNING IN CLASS XI STUDENTS OF MA NURUL CHOLIL 2 GALIS - Mariatun, Ika Lis; Samiyah (Esteem Journal of English Education Study Programme, 2025)
This study investigates efforts to enhance language learning outcomes among Class XI students of MA Nurul Cholil 2 Galis through the application of cooperative learning strategies. Implemented as Classroom Action Research (CAR), the study was conducted over two cycles, each comprising two sessions. Data collection tools included observation sheets for both teacher and student activities, interviews, field notes, and documentation. Initial findings revealed limited student engagement and low achievement levels due to the predominant use of lecture-based instruction, which led to boredom and passive participation. However, the introduction of cooperative learning methods fostered a more interactive environment, encouraging students to work collaboratively in solving problems. This shift significantly improved both participation and academic performance. The percentage of students achieving the minimum learning criteria rose from 68% in the first cycle to 82% in the second. The results indicate that cooperative learning not only promotes student involvement but also effectively supports improved learning outcomes in language instruction.